Eco-Friendly Management of Rice Striped Stem Borer Chilo Suppressalis (Walker) in Rice Crop (Journal of Agriculture and Biology, 2025)
Rice striped stem borer damage the rice crops from the seedling to crop maturity and in sever infestation result in white ear head during the reproductive stage and dead heart during the tillering stage, which causes huge yield loss up to 60.0 %. The most crucial and essential component of the IPM strategy is pest monitoring, which is consistently evaluate the population and crop damage. Thus, the present research was performed to monitor and control the RSSB by using the different trapping devices in rice filed. Attraction in different trapping devices revealed that initially adult were caught during the first week of August and increased subsequently weeks in all trapping devices up to the October. Further data showed overall maximum seasonal adult population (195.30±19.25) was caught by pheromone traps followed by light traps (101.45±14.58), yellow color sticky traps (97.50±13.25) and yellow water pan trap (53.50±09.25), respectively. Furthermore, data exhibited the highest trapping efficiency (43.71%) was observed by the installation of pheromone traps followed by light traps (22.61%), yellow color sticky traps (21.70%) and water pan trap (11.97%), respectively. In addition, impact of the treatments was observed by calculate the crop damage symptoms and minimum crop damages i.e white ears and dead hearts (09.94±1.25%) and (09.39±1.10%) were recorded pheromone traps followed by light traps (12.59±1.25%) and (11.88±1.62%), yellow color sticky trap (YCST) (17.89±1.89%) and (17.48±2.10%), and yellow water pan trap (YWPT) (25.64±2.46) and (22.81±3.23), control (42.68±7.23) and (39.03±07.12) were recorded, respectively. Furthermore, results showed the highest average yield (4865.00 kg/haˉ1) was obtained in the plots where pheromone traps were installed, followed by light traps (4608.00 kg/haˉ1), YCST (4230.50 kg/haˉ1), YWPT (4205.0 kg/haˉ1) and in control (4037.60 kg/ haˉ1), respectively. Based on the present findings, highest adult attraction, lowest crop damage and significant high yield, thus, pheromone and light traps are the convenient tools to control adults of rice striped stem borer in rice.